Rose cultivation in Cyprus under two irrigation regimes using local substrates - Chimonidou D.; Vassiliou L.; Kerkides P.; Psyhoyiou M. (Water saving in Mediterranean agriculture and future research needs [Vol. 2], 2007)
Roses cv Eurored were cultivated on four different substrates in a heated greenhouse, using local materials i.e. perlite 100 percent, mixtures of perlite 50 percent with pomace 50 percent, perlite 50 percent with almond shells 50 percent and almond shells 50 percent with pine bark 50 percent. The two irrigation regimes applied were 800 ml and 530 ml. The photosynthetic rate, stomatal conductance, CO2 concentration and transpiration rate of the rose plants grown in the four substrates and under the two irrigation regimes were measured as well as the total productivity and quality characteristics of the roses produced. Results showed that concerning the interaction between substrate and irrigation level, higher production was recorded with the roses growing in the substrate pine bark 50 percent and almond shells 50 percent irrigated with the reduced irrigation level and the substrate of perlite 50 percent and pomace 50 percent irrespective of irrigation level. The quality characteristics of the roses produced under all treatments were marketable with mean stem length between 75-85 cm. No significant differences were observed concerning the photosynthetic rate, the stomatal conductance, the CO2 concentration and the transpiration rate under the four substrates and the two levels of irrigation. It seems that the lower irrigation level did not create conditions of water stress and did not affect negatively the physiological activities of the rose plants.
Proceedings of the International Conference WASAMED Project (EU contract ICA3-CT-2002-10013), 2007/02/14-17, Valenzano (Italy)